Crop geometry and nitrogen management impacts on cotton cultivar H-1098(i) productivity - MALIK, KAPIL; MEHTA, A K; THAKRAL, S K; ABHILASH, ABHILASH (The Indian Journal of Agricultural Sciences, 2019)
A field investigation was undertaken to study plant geometry and nitrogen management on performance of cotton variety H-1098 (i). The experiment was conducted during kharif 2015 at CRS, Sirsa, Haryana, in split plot design with 3 replications consisting of four spacing of cotton crop in main plots while four levels of nitrogen in subplots. Experimental results revealed that among different crop geometries, significantly higher plant population, plant height and LAI was observed with 67.5 cm × 10 cm spacing than rest spacing’s treatments however weight of boll was not affected by different plant geometry. Wider spacing (67.5 cm × 30 cm) had higher dry matter accumulation, sympodial branches and number of bolls per plant but yield of seed cotton was recorded highest under 67.5 cm × 15 cm spacing than recommended spacing (67.5 cm × 30 cm). Periodic growth parameters like plant height and leaf area index (LAI) significantly increased with 25% increase in nitrogen dose over recommended dose of nitrogen however plant population was not significantly influenced by different nitrogen doses. Higher dry matter accumulation observed with 150% recommended dose of nitrogen over rest of treatments but number of sympodial branches was maximum at 100% of recommended nitrogen dose which remained statistically at par with further increased in nitrogen doses. Seed cotton yield and the number of bolls/plant increased significantly with 125% RDN over 100% and 75% of recommended nitrogen dose.